PENGARUH UNIT PRODUKSI, PRAKERIN, PRESTASI BELAJAR DAN DUKUNGAN KELUARGA TERHADAP KESIAPAN KERJA SISWA SMK NEGERI 10 SURABAYA - Hartati, Siti Alfiyah (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
This study aims to determine: readiness for working students Vocational High School (SMK) in SMK Negeri 10 Surabaya, and the effect of: the practical activities of production units, the experience of working practices of industrial, academic achievement and family support individually or jointly against job readiness of students in SMK Negeri 10 Surabaya. This study population is vocational students of class XI and XII at SMK Negeri 10 Surabaya Academic Year 2014-2015 with a sample of 110 students. The samples using proportional cluster random sampling technique. Relationships and the influence of each independent variable on the dependent variable was analyzed with multiple regression statistics. The results of descriptive analysis showed that each variable indicators showed high criteria. Hypothesis testing results show that there is a partial effect of each independent variable on the dependent variable. Likewise, there are significant simultaneous production unit between the practical activities of the school, prakerin experience, academic achievement and family support for job readiness. It is clear that the practical activities in the school production units, prakerin experience, academic achievement and family support together may be able to explain variants job readiness of students in SMK Negeri 10 Surabaya